Collaborative design in virtual environments - Wang, Xiangyu 1979-.; Tsai, Jerry Jen-Hung.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Collaborative virtual environments (CVEs) are multi-user virtual realities which actively support communication and co-operation. This book offers a comprehensive reference volume to the state-of-the-art in the area of design studies in CVEs. It is an excellent mix of contributions from over 25 leading researcher/experts in multiple disciplines from academia and industry, providing up-to-date insight into the current research topics in this field as well as the latest technological advancements and the best working examples. Many of these results and ideas are also applicable to other areas such as CVE for design education. Overall, this book serves as an excellent reference for postgraduate students, researchers and practitioners who need a comprehensive approach to study the design behaviours in CVEs. It is also a useful and informative source of materials for those interested in learning more on using/developing CVEs to support design and design collaboration.
pt. 1. Virtual environments for design : fundamentals -- pt. 2. Representation and embodiments in collaborative virtual environments : objects, users, and presence -- pt. 3. Design cooperation : sharing context in collaborative virtual environments -- pt. 4. How designers design in collaborative virtual environments -- pt. 5. Case studies
Electronic reproduction.
Keywords: Shared virtual environments; Electronic books